Comparison of dislocation content measured with transmission electron microscopy and micro-Laue diffraction based streak analysis. (February 2018) - Zhang, C.; Balachandran, S.; Eisenlohr, P.; Crimp, M.A.; Boehlert, C.; Xu, R.; Bieler, T.R.
Abstract: The subsurface dislocation content in a Ti-5Al-2.5Sn (wt%) uniaxial tension sample deformed at ambient temperature was characterized by peak streak analysis of micro-Laue diffraction patterns collected non-destructively by differential aperture X-ray microscopy, and with focused ion beam transmission electron microscopy of material in the same volume. This comparison reveals that micro-Laue diffraction streak analysis based on an edge dislocation assumption can accurately identify the dominant dislocation slip system history (Burgers vector and plane observed by TEM), despite the fact that dislocations have predominantly screw character. Other dislocations identified by TEM were not convincingly discernible from the peak streak analysis. Graphical Abstract: